Source monitoring in Korsakoff's syndrome: "Did I touch the toothbrush or did I imagine doing so?". (June 2017) - El Haj, Mohamad; Nandrino, Jean Louis; Coello, Yann; Miller, Ralph; Antoine, Pascal
Abstract: There is a body of research suggesting compromised ability to distinguish between different external sources of information (i.e., external monitoring) in Korsakoff's syndrome. Here we replicate and extend this literature by assessing the ability of patients with Korsakoff's syndrome to distinguish between different external sources of information (i.e., external monitoring), between internal and external sources of information (i.e., reality monitoring), and between different internal sources of information (i.e., internal monitoring). On the external monitoring assessment, patients with Korsakoff's syndrome and controls watched the experimenter place objects (e.g., a toothbrush) in either a black or white box; afterward, they were asked to remember where the objects had been placed. On the reality monitoring assessment, participants had to either place objects or watch the experimenter place objects in a black box; afterward, they were asked to remember whether the objects had been placed in the box by themselves or by the experimenter. On the internal monitoring assessment, participants had to either place objects or imagine themselves placing objects in a black box; afterward, they were asked to remember whether they had previously placed the objects in the box or imagined doing so. Analyses demonstrated lower external and internal monitoring in patients with Korsakoff's syndrome than in controls, but no significant difference was observed between the two populations on the reality monitoring condition. Our data provide preliminary evidence that the ability to recognize oneself as the author of one's own actions may be relatively preserved in Korsakoff's syndrome.